Structure And Authority of The Shariah Court A Comparative Study Between Aceh and Penang - Wahyudi; Susantri, Yulia; Maslijar, Heri; Rizki, Darlin (Universitas Islam Negeri Alauddin Makassar, 2026)
This study examines the institutional structure and authority of the Aceh Syar’iyah Court in Indonesia and the Penang Shariah Court in Malaysia as two models of implementing Islamic law within different national legal systems. Previous studies on Sharia courts in Southeast Asia have largely focused on normative and institutional aspects, with limited attention to how constitutional design shapes the scope of judicial authority in a direct comparative framework. This study argues that the differences in the authority of Sharia courts in Aceh and Penang are fundamentally influenced by constitutional structure and the distribution of state power in each country. This research employs normative legal research with a comparative approach through the analysis of laws and regulations, Aceh qanun, Penang state enactments, and relevant scientific literature. The findings show that the Aceh Syar’iyah Court has broader authority, including in the field of Islamic criminal law (jinayah), as a consequence of Aceh’s status as a special autonomous region within a unitary state. In contrast, the Penang Shariah Court has more limited authority due to the constraints of the Malaysian federal system, particularly in the field of criminal jurisdiction. This study contributes theoretically by providing a constitutional-based comparative analysis that explains the relationship between state structure and the scope of Sharia court authority, thereby enriching the study of constitutional law and Islamic judiciary in Southeast Asia.